MEASURING THE KNOWLEDGE, ATTITUDE, SKILLS AND ASPIRATIONS OF COCOA FARMERS TOWARDS THE USE OF PESTICIDES - Angela Otiwaa Acheampong; Enoch Kwame Tham-Agyekum; Fred Ankuyi; Fred Nimoh; Ernest Laryea Okorley; John-Eudes Andivi Bakang; Justice Frimpong-Manso (Socio-Economics/Agribusiness Department, 2023)
Identifying the scope of pesticide safety by examining farmers’ knowledge, attitudes, skills and aspiration (KASA) is a key step in developing suitable training strategies. Additionally, figuring out what influence’s farmers' KASA concerning pesticides might be a crucial step in developing sustainable legislation and initiatives. Here, we tested the hypothesis that farmers’ KASA is influenced by their socio-economic characteristics. We sampled 364 cocoa farmers using the multi-stage sampling procedure and analyzed the data using descriptive and inferential statistics. For knowledge, we found sex, years of experience in cocoa farming, access to extension services, and cooperative membership to be the key drivers. The following factors have a statistically significant effect on attitude: marital status, access to extension, membership in cooperatives and participation in training programmes. Eight variables: sex, years of education, farming experience, age of the cocoa farm, access to extension, access to premium, membership in cooperatives, and participation in training programs had a significant influence on farmers’ skills in safe pesticide usage. Sex, marital status, farming experience, farm age, access to extension and the number of extension contacts are the factors that influence farmers' aspirations for the safe use of pesticides. Our study advocates for maintaining or enhancing the KASA status of cocoa farmers regarding pesticide use through consistent extension activities with cooperative groups by the Ghana Cocoa Board.